Tingkat Kepatuhan Kapal Perikanan terhadap Eksploitasi Kawasan Konservasi Kepulauan Anambas - Dani Prana Dinata; Achmad Kusyairi; Alif Astagia (Mikroba : Jurnal Ilmu Tanaman, Sains Dan Teknologi Pertanian, 2025)
Marine conservation areas play a crucial role in maintaining the sustainability of aquatic ecosystems and fishery resources. However, many fishing vessels still violate regulations by entering and exploiting conservation areas without permission. This study aims to analyze the compliance level of fishing vessels with conservation regulations in the Anambas Islands, identify the factors contributing to non-compliance, and evaluate the effectiveness of the imposed sanctions. The research employs a qualitative and quantitative descriptive approach, utilizing SWOT analysis to assess internal and external factors affecting compliance. Data were collected through vessel movement monitoring using the Vessel Monitoring System (VMS), interviews with fishery inspectors, and analysis of relevant policy documents. The findings indicate that many fishing vessels fail to comply with conservation regulations, mainly due to fish migration into conservation areas, deliberate violations by business operators seeking higher profits, and a lack of understanding among captains regarding conservation boundaries. Additionally, limited human resources and monitoring facilities hinder effective law enforcement. Although sanctions are regulated under Government Regulation No. 85 of 2021, their effectiveness remains low, as evidenced by recurring violations. Therefore, strengthening supervision, optimizing monitoring technology, and raising fishermen’s awareness of conservation regulations are necessary to enhance compliance among fishing vessels and preserve marine ecosystems.